2001
DOI: 10.1107/s1600536801000733
|View full text |Cite
|
Sign up to set email alerts
|

Tricoccin R6

Abstract: The X‐ray crystal structure of the title compound, C25H28O8, has been determined. In the structure, both the terminal five‐membered rings (A and F) are planar. The fused five‐membered rings C and E are in envelope conformations, and ring B is in a slightly distorted half‐chair conformation. The six‐membered ring D is in a slightly distorted sofa conformation. The structure is stabilized by O—H⋯O hydrogen bonds and C—H⋯O inter‐ and intramolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During a comparative study of the molecular structure of Tricoccin R6 (Abdul Ajees et al, 2001) with that of the related compound Tricoccin R2 (Sekar et al, 1996) it was found that the geometry of the molecules in the two structures agreed well except in the region of ring F of Tricoccin R2. This could be traced to a wrong assignment of two of the atoms in ring F of Tricoccin R2.…”
Section: Commentmentioning
confidence: 99%
“…During a comparative study of the molecular structure of Tricoccin R6 (Abdul Ajees et al, 2001) with that of the related compound Tricoccin R2 (Sekar et al, 1996) it was found that the geometry of the molecules in the two structures agreed well except in the region of ring F of Tricoccin R2. This could be traced to a wrong assignment of two of the atoms in ring F of Tricoccin R2.…”
Section: Commentmentioning
confidence: 99%